Heterochromatin Is Not the Only Place for satDNAs: The High Diversity of satDNAs in the Euchromatin of the Beetle Chrysolina americana (Coleoptera, Chrysomelidae) - Rico-Porras, José M.; Mora, Pablo; Palomeque, Teresa; Montiel, Eugenia E.; Cabral-de-Mello, Diogo C. [UNESP]; Lorite, Pedro (MDPI, 2024)
The satellitome of the beetle Chrysolina americana Linneo, 1758 has been characterized through chromosomal analysis, genomic sequencing, and bioinformatics tools. C-banding reveals the presence of constitutive heterochromatin blocks enriched in A+T content, primarily located in pericentromeric regions. Furthermore, a comprehensive satellitome analysis unveils the extensive diversity of satellite DNA families within the genome of C. americana. Using fluorescence in situ hybridization techniques and the innovative CHRISMAPP approach, we precisely map the localization of satDNA families on assembled chromosomes, providing insights into their organization and distribution patterns. Among the 165 identified satDNA families, only three of them exhibit a remarkable amplification and accumulation, forming large blocks predominantly in pericentromeric regions. In contrast, the remaining, less abundant satDNA families are dispersed throughout euchromatic regions, challenging the traditional association of satDNA with heterochromatin. Overall, our findings underscore the complexity of repetitive DNA elements in the genome of C. americana and emphasize the need for further exploration to elucidate their functional significance and evolutionary implications.
Keywords: CHRISMAPP; chromosome in silico mapping; Chrysomelidae; euchromatin; fluorescence in situ hybridization; genome evolution; heterochromatin; karyotype; repetitive DNA; satellite DNA; satellitome